Flash Solid–Solid Synthesis of Silicon Oxide Nanorods. Issue 35 (5th August 2020) - Yan, Xiaoliang; Sun, Wei; Wang, Wu; Duchesne, Paul N.; Deng, Xiaonan; He, Jiaqing; Kübel, Christian; Li, Ruifeng; Yang, Deren; Ozin, Geoffrey A.
Abstract: 1D silicon‐based nanomaterials, renowned for their unique chemical and physical properties, have enabled the development of numerous advanced materials and biomedical technologies. Their production often necessitates complex and expensive equipment, requires hazardous precursors and demanding experimental conditions, and involves lengthy processes. Herein, a flash solid–solid (FSS) process is presented for the synthesis of silicon oxide nanorods completed within seconds. The innovative features of this FSS process include its simplicity, speed, and exclusive use of solid precursors, comprising hydrogen‐terminated silicon nanosheets and a metal nitrate catalyst. Advanced electron microscopy and X‐ray spectroscopy analyses favor a solid–liquid–solid reaction pathway for the growth of the silicon oxide nanorods with vapor–liquid–solid characteristics. Abstract : A flash solid–solid process, triggered by hydrogen‐terminated silicon nanosheets and nickel or cobalt nitrate, is explored to synthesize silicon oxide nanorods within a few seconds.